Experimental study on dynamic tensile mechanical properties and energy dissipation of GFRP tube-mortar specimens with different hollow ratios - Nao Lv; Qi Zong; Liang Xie; Jian Guo; Shihai Guo; Ziyi Lu; Deling Gao; Haibiao Xu; Hao Wang (Scientific Reports)
Abstract The mechanical properties and energy dissipation evolution of GFRP tube-mortar under dynamic tensile load were investigated based on experiments. The influence of GFRP tube wall thickness and hollow ratio on the peak stress, energy dissipation and failure form of GFRP tube was analyzed by using SHPB test device. The results show that: (1) The dynamic tensile peak stress of GFRP tube-mortar specimens is increased by the restraint protection of GFRP tubes, and the increase of stress is more significant with the tube wall thickness. The presence of hollow ratio will degrade the specimen and reduce its dynamic tensile strength, and the greater the hollow ratio, the more significant the stress reduction of the specimen. (2) Both the wall thickness growth factor and the hollow ratio growth factor are greater than 1, and the increase of the wall thickness and the decrease of the hollow ratio will increase the dynamic tensile strength. The restraint protection of GFRP tube not only enhances the mechanical properties of mortar, but also reduces the weakening of mortar properties caused by internal holes. (3) The presence of GFRP tube significantly reduces the degree of fracture and breakage, and the greater the thickness of the tube wall, the lower the overall degree of fracture and breakage, the stronger the deformation resistance and the higher the stability. The existence of the hollow ratio will produce stress concentration inside the specimen and increase the degree of breakage. (4) The reflection energy and dissipative energy decrease with the increase of GFRP tube wall thickness, and the transmission energy increases with it. The increase of hollow ratio will enhance the energy dissipation effect of the specimen. For mortar concrete buildings, the restraint protection effect of GFRP tubes can greatly improve the dynamic load resistance of the structure, reduce the damage degree of the structure, and improve the safety performance of the building structure. At the same time, reducing the hollow-ratio of the structure itself can enhance the safety performance of the building structure.